Potential of Cashew Apples as Valuable Raw Materials in Food Industry and Biotechnology in Africa: A Review - ADJOU, Sènan Euloge; GBAGUIDI, AHOTONDJI BERTIN; Dègnon, René G.; DAHOUENON-AHOUSSI, Edwige; SOUMANOU, MOHAMED; Dominique C. K. Sohounhloue, Dominique C. K. (My University, 2017)
The possibility for biomass valorization, using biotechnological processes, is an ideal solution for the use of agricultural products with low commercial value. Cashew apple is an agricultural resource available in many African countries. Unfortunately, this agricultural resource is abandoned in the fields by the producers and decayed each year in large quantities, because of the astringency of the juice, and the consumption of cashew apples with milk, would be considered incompatible in several African countries. However, there are a lot of ways to upgrade the value of this resource as a raw material in food industry or in the production of renewable bioenergy. Technical methods used involve biotechnological processes using enzymatic biocatalysis, fermentation and fractional distillation.
Keywords: Cashew apple; Valorization; Biotechnological processes; Renewable BioEnergy